2019
DOI: 10.3390/ma12132127
|View full text |Cite
|
Sign up to set email alerts
|

Improved NOx Storage/Release Properties of Ceria-Based Lean NOx Trap Compositions with MnOx Modification

Abstract: Ceria/spinel-based lean NOx trap compositions with and without barium were modified with MnOx via incipient wetness impregnation. The effect of the MnOx layer on the aged materials (850 °C) as to the NOx storage and release properties was investigated via NOx adsorption (500 ppm NO/5% O2/balance N2) carried out at 300 °C in a dual-bed with a 1% Pt/Al2O3 catalyst placed upstream of the samples to generate sufficient amounts of NO2 required for efficient NOx storage. Subsequent temperature programmed desorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…CeO 2 provides high oxygen storage abilities and enhances redox properties. 93 The hollow structure of silica was etched to hold MET. In vitro drug release studies of MET from MET-HMSN-CeO 2 NPs developed by Zhong et al have indicated that, at 24 hours, only 40% of the total drug is released from MET-HMSN-CeO 2 NPs, thus implying sustained release of MET.…”
Section: Research Progress In Nanoplatforms In the Treatment Of Dnmentioning
confidence: 99%
See 1 more Smart Citation
“…CeO 2 provides high oxygen storage abilities and enhances redox properties. 93 The hollow structure of silica was etched to hold MET. In vitro drug release studies of MET from MET-HMSN-CeO 2 NPs developed by Zhong et al have indicated that, at 24 hours, only 40% of the total drug is released from MET-HMSN-CeO 2 NPs, thus implying sustained release of MET.…”
Section: Research Progress In Nanoplatforms In the Treatment Of Dnmentioning
confidence: 99%
“… Combined antioxidative with antidiabetic activities, nanoparticle administration can exhibit specially nephroprotective ability without causing major side effects. Tong et al 91 Schöneborn et al 93 3.3 Nanometals and Nanoalloys AuNPs Au Kidney AuNPs prevents TNF-α over expression while reduces the renal oxidative stress by increasing the activities of renal SOD and catalase and by reducing the tissue MDA level and can stay in the blood circulation for a longer period of time. AuNPs prevents the adverse effects of hyperglycemia in renal tissue by preventing the accumulation of ECM proteins and the amelioration of podocyte injury without showing no cytotoxicity in human cells.…”
Section: Introductionsmentioning
confidence: 99%
“…In combination, aftertreatment methods of NO x mitigation including lean NO x traps (LNTs) and selective catalytic reduction (SCR) are used. LNTs store NO x on the surface of a catalyst washcoat during lean operation, which is then released and reduced to nitrogen catalytically during a rich regeneration phase [10]. In comparison, SCR is a more straightforward technology, where a urea solution injected into the exhaust stream forms ammonia that reacts with NO x to form nitrogen and water [10].…”
Section: Introductionmentioning
confidence: 99%
“…LNTs store NO x on the surface of a catalyst washcoat during lean operation, which is then released and reduced to nitrogen catalytically during a rich regeneration phase [10]. In comparison, SCR is a more straightforward technology, where a urea solution injected into the exhaust stream forms ammonia that reacts with NO x to form nitrogen and water [10]. SCR systems add complexity since they need on-board tanks for urea storage and require frequent refilling.…”
Section: Introductionmentioning
confidence: 99%